An Associative Image of Ukrainian Students - Samiilyk, Svitlana (East European Journal of Psycholinguistics, 2016)
The article describes an associative image of such a social group as students of Ukraine, particularly the students of higher educational institutions of different regions of the country: Zhytomyr Ivan Franko State University, Hryhoriy Skovoroda Pereyaslav-Khmelnytskyi State Pedagogical University, Kyiv National University of Trade and Economics, Lviv Polytechnic National University, Ivan Franko National University of Lviv, and Donetsk National University. The associations were collected during 2015 – 2016. For this purpose, one of the most popular methods in psycho- and cognitive linguistics, a free word association test, was used. References Батурина Л. И. Российский ассоциативный портрет современной рекламы // Язык, сознание, коммуникация: Сб. статей / Ред. В. В. Красных, А. И. Изотов. . М. : Диалог – МГУ, 1999. – Вып. 7. – С. 85–99. Baturina, L. I. (1999) Rossiiskii assotsyativnyi portret sovremennoi reklamy [Russian associative picture of modern advertisement]. Yazyk, Soznaniye, Kommunikatsiya, 7, 85–99. Горошко Е. И. Специфика ассоциативного сознания некоторых групп русскоязычного населения Украины / Е. И. Горошко // Языковое сознание: формирование и функционирование. – М. : Ин-т языкознания РАН, 1998. – С. 186–200. Goroshko, Ye. I. (1998). Spetsyfika assotsyativnogo soznaniya niekotorykh grupp russkoiazychnogo naseleniya Ukrainy [The specific character of some Russian-speaking groups’ consciousness of Ukrainian people]. Yazykovoye Soznaniye: Formirovaniye i Funktsyonirovaniye, 186–200. Караулов Ю. Н. Типы коммуникативного поведения носителя языка в ситуации лингвистического эксперимента / Ю. Н. Караулов // Этнокультурная специфика языкового сознания. – М. : Институт языкознания РАН, 1996. – C. 67–98. Karaulov, Yu. N. (1996) Tipy kommunikativnogo povedeniia nositelia jazyka v sytuacyi lingvistichedkodo eksperimenta [The types of communication behaviour of a native languagespeaker in the linguistic experiment situation]. Etnokulturnrya Spetsyfika Yazykovogo Soznaniya. Moscow: Institute of Linguistics of the Russian Academy of Sciences, 67–98. Недашківська Т. Є., Самійлик С. В. Проблема формування стимульного списку для психолінгвістичного дослідження / Т. Є. Недашківська, С. В. Самійлик // Психолінгвістика : [зб. наук. праць. ДВНЗ «Переяслав-Хмельницький державний педагогічний університет імені Григорія Сковороди»]. – Пререяслав-Хмельницький : ФОП Лукашевич О. М., 2015. – Вип. 18 (2). – С. 61–73. Nedashkivska, T. Ye. & Samiilyk, S. V. (2015). Problema formuvannia stymulnoho spysku dlia psykholinhvistychnoho doslidzhennia [The issue of stimulus list forming for a psycholinguistics research]. Psycholingvistyka, 18(2), 61–73. Салихова Э. А. Лингвокультурологическая составляющая ассоциативного портрета билингва // Вестник Башкирского университета. – № 3. – Том 11. – 2006. – С. 74–78. Salikhova, E. F. (2006) Lingvokulturologicheskaia sostavliayushaia assotsyativnogo portreta bilingva [Linguocultural Element of An Associative Image of a Bilingual Person]. – Scientific Issues of Bashkirsky University, 11(3), 74–78. Сукаленко Т. М. Асоціативне поле жінки в українській мовній свідомості / Т. М. Сукаленко // Наукові праці Кам’янець-Подільського національного університету імені Івана Огієнка. Філологічні науки. – 2009. – Вип. 20. – С. 639–642. – Режим доступу: http://nbuv.gov.ua/UJRN/Npkpnu_fil_2009_20_171 Sukhalenko, T. M. (2009) Asotsiatyvne pole zhinky v ukrainskii svidomosti [The Associative Field of Woman in Ukrainian Consciousness] – Scientific Issues of Ivan Ohiyenko Kamianets Podilsky National University, 20, 639-642. Retrieved from: http://nbuv.gov.ua/ UJRN/Npkpnu_fil_2009_20_171. Терехова Д. І. Асоціативний портрет українця та росіянина / Д. І. Терехова // Мовознавство. – 1997. – № 6. – С. 43–50. Terekhova, D. I. (1997) Asotsiatyvnyi portret ukraintsia i rosiianyna [An associative portrait of a Ukrainian and a Russian]. Movoznavstvo, 6, 43–50.